ATRIBUT KEPUASAN KONSUMEN PRODUK MINUMAN RINGAN COCA COLA DI KOTA BANDARLAMPUNG - Yustitia, Adrina (Jurnal Teknologi & Industri Hasil Pertanian, 2012)
The Objective of this research is to analyze the attributes that influence Coca Cola customer satisfaction. Gap analysis shows that the priority attributes must be improved performance were: interesting promotion (-0.83), color of the product (0.61), attractive design (-0.59), refill packaging (-0.58) and product safety (-0.08) while the other attributes have accordanced with customer expectations. Importance-Performance Analysis showed the top priority attributes (quadrant A) were an interesting campaign, the next priority for the enhanced importance (quadrant C) were the product color, attractive design, packaging, rechargeable and affordable prices. Coca Cola has been able to meet consumer expectations in reaching the level of satisfaction ( multi-attribute test : 1.78, total value of satisfaction (13,508). Keywords: attributes, coca cola, consumer expectations